Enterprise Architecture With . NET Expert-Backed Advice for Information System Design, down to . NET and C# Implementation - Gouigoux, Jean-Philippe (Packt Publishing, Limited, 2024)
The software development domain continues to grow exponentially, and information systems have become the backbone of most industries, including non-digital-native ones. However, technical debt, coupling, and a high level of maintenance - sometimes bringing IT systems to a complete halt - continue to present a problem. The software industry has to still apply standards-based, modular, and repeatable approaches that exist in other industries. This book demonstrates such methods in action, particularly business/IT alignment principles. As you progress, you'll cover advanced concepts and theories currently researched in academia. Then, you'll be guided toward a practical framework to transfer these approaches to actual software architecture. Finally, a dedicated section will help you apply the knowledge you gain to a sample application in .NET where API design, dependency management, and code writing will be explained in detail to relate to the business-alignment principles explained at the beginning. Throughout the book, you'll get equipped with the skills to create modular, long-living applications that serve your users better. By the end of this .NET book, you'll not only have learned new concepts but also gained the ability to apply them immediately to your upcoming software endeavors.
Description based upon print version of record. - The concept of technical debt
Keywords: Software architecture; C# (Computer program language); Architecture logicielle; C# (Langage de programmation)